Implementation of Vision Therapy at a Youth Rehabilitation Facility. - Schnell, Pamela H.; Prattas, Vassiliki N. (Optometry & Visual Performance, 2022)
In the United States, there is an increasing number of teenagers and youth who are experiencing mental health, emotional, or behavioral disorders. Treatment for these disorders ranges from outpatient, one-on-one counseling to group therapy to inpatient hospital admission. Residential youth rehabilitation facilities, where adolescents receive around-the-clock care and supervision, are one option for intensive treatment. Many youth rehabilitation facilities have onsite medical clinics, but few offer optometric vision therapy as an included aspect of care. One residential rehabilitation facility for at-risk youth, Youth Villages, does offer full-scope optometric care, including vision therapy, to its residents, in partnership with Southern College of Optometry. The six case summaries included here outline some of the unique challenges faced in implementing vision therapy in an unconventional clinical setting, including psychiatric, attentional, and behavioral obstacles, as well as administrative issues, that can affect performance in vision therapy and its overall efficacy. Despite the hurdles that arise in such a facility, there is significant potential for positive vision therapy outcomes, and the opportunity is vast to provide care for youth in great need.